Revisiting changing climatic conditions in the North Ossetia mountainous zone and their impact on erosion processes - S. E. Kuchiev; Kh. M. Khetagurov (Новые технологии)
Currently, there are many scientific publications concerning changes in climatic conditions of individual regions, countries, continents and the entire earth as a planet. This fact has led us to consider these changes regarding their impact on the development of erosion processes in mountain conditions. The basis was the research presented in S.E Kuchiev’s PhD thesis of 1996-1998, as well as the verification of hypotheses put forward in the research on the development of erosion processes. The above mentioned required the continuation of research in the second period from 2008 to 2013. On average, 605 mm fell during the years of research, 478 mm in the first period 1996-1998, 668 mm in the second 2008-2013, and from 2 to 8 rains with an intensity of more than 20 mm fell in different years.The correlation analysis shows that with the increase in precipitation observed in recent years, there is a correlation with the amount of heavy rainfall. During the period under review, there were 27 to 48 rains with an intensity above 5 mm. In 2009 heavy rainfall was characterized mainly by an intensity of 20 to 40 mm per day, but in August 2009 and 2010, 71 and 73 mm each fell. The peak of heavy rains was noted in 2012, when in June it rained two days in a row with an intensity of 121 and 101 mm.The indicator of surface runoff has significantly increased, both in the control variant (pure steam) and in rotation crops, which can be arranged in ascending order of their erosion resistance: row crops, cereals of the continuous sowing method and perennial grasses. The research was carried out at the mountain long-term station of the SCNII–GPSH – a branch of the VNC RAS in the village of Dargavs.